The Nature and Prevalence of Impulsive Behaviour in a South African University Sample - Naidoo, Sarojini (Southern African Journal of Social Work and Social Development, 2025)
Impulsive behaviour is a concerning phenomenon, closely linked to a range of adverse mental and physical health outcomes. It often manifests in risky sexual behaviour, excessive alcohol consumption, and reckless driving. University students appear particularly vulnerable to such behaviours, as they navigate the transition from high school to university and experience increased autonomy in their decision-making. Research has shown that economic and social inequality are key drivers of risky behaviour among young adults in developing societies, including African contexts, yet there is a lack of prevalence data, and much of the existing literature tends to focus primarily on risky sexual behaviour and substance use. This highlights the need to explore the nature and prevalence of other forms of risky behaviour within this context. The present study aimed to explore the prevalence and nature of impulsive behaviour in a sample of university students in South Africa. Using a quantitative approach and a cross-sectional design, the study recruited 532 psychology students aged 18–35 years from a South African university. The Impulsive Behaviour Scale (IBS) was administered across three year groups in a group setting. Data were analysed using SPSS Version 28, revealing a high prevalence rate (90%) of impulsive behaviour in the sample, with no significant gender differences. The most frequently endorsed behaviours included risky sexual activity, self-harm, impulsive spending, and excessive alcohol consumption. The findings have important implications for social workers and other mental health practitioners in the South African context.